Empirical Analysis of African Aubergine (Solanum gilo) – Marketing and Income Disparity among Traders in Owerri, Imo State, Nigeria - Godfrey C. Onuwa (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
African Aubergine is an indigenous tropical crop cultivated in Nigeria. Agricultural marketing creates incentives that accelerate the promotion of further production and consumption of harvested produce. Therefore, this study analysed African Aubergine marketing and income disparity among traders in Owerri, Imo State, Nigeria. Primary data collected via multistage sampling from ninety-five (95) respondents was analysed using descriptive statistics, marketing margin and efficiency analysis, Ordinary Least Square regression and Gini Coefficient index. The results show that the mean age, years spent in school, household size, trading experience and quantity of bags sold were 37 years, 8 years, 7 people, 9 years and 8 bags per month, respectively. The estimated marketing margin and efficiency index were ₦1,250 and 0.36, respectively. The estimated coefficients of Ordinary Least Square regression (R2) were 0.773. Thus, the variables (marketing experience, cost price, quantity sold and marketing cost) in the regression model accounted for 77% of the variation in the marketing margin of African Aubergine traders in the study area. The estimated Gini Coefficient was 0.59, indicating a moderate level of income disparity (inequality) in the sales income of the respondents. Several marketing constraints were observed in the study area. Therefore, this study recommends improved credit access and market information dissemination, commodity cost subsidisation, storage technology adoption, market infrastructure development and interventions, commodity price control and policy modification that regulates market activities.